Η αρχαιολογία της Μικράς Ασίας και η βρετανική αρχαιολογική σχολή Αθηνών - Κοσμόπουλος Μιχαήλ Β. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1986)
The British School of Archaeology at Athens was established in 1886, and the Annual of the British School at Athens (abbr. BSA ) was published for the first time in 1895-96. The interest of the School in the history and archaeology of Asia Minor has always been vivid and demonstrated by several excavations and researches. This interest was especially strong in the first two decades of our century and in the late 50’s, as can be seen from the articles published in the BSA (fig. 1). Most of the articles on Asia Minor have been writen by prominent members of the School, like F. W. Hasluck, J. Cook, W. Leaf, H. Ormerod, and A. M. Woodward. These articles deal with a wide range of subjects, including ancient topography, history of religion, and archaeology (architecture, pottery, excavation reports, and notes on numismatics and inscriptions), since prehistoric times; emphasis has, however, been given to the Classical and Roman periods. Of special interest are Flasluck’s articles on Anatolian folklore and the Medieval monuments of Asia Minor and his studies on ancient and modern religions. J. M. Cook has written about the pottery and topography of Ionia and scholars like Leaf, Ormerod, and Woodward dealt with the topography and the Greek inscriptions from various places of Asia Minor. Most of the articles have been written about Smyrna, Constantinople, and Halikarnassos. The multivariate researches and studies of the British scholars have seriously increased our knowledge of the history of Asia Minor. They are especially important for the study of Greek culture and life in Asia Minor over a period of more than three thousand years, from prehistory to modern times.